2016
DOI: 10.1111/trf.13519
|View full text |Cite
|
Sign up to set email alerts
|

Inactivation of dengue, chikungunya, and Ross River viruses in platelet concentrates after treatment with ultraviolet C light

Abstract: Our study has shown that DENV, CHIKV, and RRV, spiked into BC-derived PLT concentrates, were inactivated by the THERAFLEX UV-Platelets system to the limit of detection of our assay, suggesting that this system could contribute to the safety of PLT concentrates with respect to these emerging arboviruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
63
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 40 publications
5
63
0
1
Order By: Relevance
“…It has been demonstrated that UVC treatment significantly reduces the infectivity of platelet products contaminated by disease‐causing bacteria, viruses, and protozoa. In addition, THERAFLEX UV‐Platelets inactivates contaminating donor WBCs while preserving platelet function and coagulation factors …”
mentioning
confidence: 99%
“…It has been demonstrated that UVC treatment significantly reduces the infectivity of platelet products contaminated by disease‐causing bacteria, viruses, and protozoa. In addition, THERAFLEX UV‐Platelets inactivates contaminating donor WBCs while preserving platelet function and coagulation factors …”
mentioning
confidence: 99%
“…In the future, other approaches may be used, for example, PI, particularly in areas endemic for dengue. The Theraflex UV-Platelets System (MacoPharma) has been shown to inactivate DENV in spiked platelet units to the limit of detection of the assay used [19], as has the Theraflex-MB Plasma System (MacoPharma) for DENV spiked into plasma [20]. Similarly the Intercept Plasma Inactivation System (Cerus Corporation) demonstrated inactivation of DENV in spiked plasma to the limit of detection [21].…”
Section: Discussionmentioning
confidence: 99%
“…Andere umhüllte Viren wie Dengue Virus (DENV) 1-4, ChikungunyaVirus (CHIKV), Ross River Virus (RRV) und Zikavirus (ZIKV) wurden ebenfalls gut inaktiviert [128,131].…”
Section: Unerwünschte Effekte Der Pathogeninaktivierung Mit Mirasol®unclassified